Implementasi Kebijakan Penerimaan Peserta Didik Baru dengan Sistem Zonasi pada SMP Negeri 12 Bandung - Elsya Rahmalia Hidayat; Agistia Nurbani Rajaba; Silmi Asy-Syifaa; Agni Nazwa N (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research aims to analyze the implementation of the New Student Admissions (PPDB) policy which uses a zoning system at SMPN 12 Bandung. This policy aims to increase equal access to education in society. To achieve this aim, this research applies a qualitative approach, which is considered effective for exploring in-depth information about the experiences and perspectives of the parties involved. Data was collected through direct interviews with resource persons from the student affairs section of SMPN 12 Bandung. This method allows researchers to gain a clearer understanding of the implementation of the zoning system in the PPDB process at the school. This research also aims to evaluate the extent to which zoning policies are effective in increasing access to education, reducing social disparities, and identifying the challenges and opportunities faced by schools in their implementation. It is hoped that the results of this research can provide recommendations for the government and related parties to improve and perfect zoning-based PPDB policies in the future.